Computarized Axial Tomography in Diagnosis of Pancreatic Cancer - Boschi, Jorge; Leborgne, José H; Leborgne, Félix; de Tényi, Andrés (Cirugía del Uruguay, 1981)
The results of computed pancreatic tomography are at present satisfacto·ry. It is a simple, non invasive, low risk method, capable of being improved day after day by new knowledge. Consequently it affords a means for quick and sáfe diagnosis of pancreatic cancer.